The Legitimacy of Medical Treatment What role for the medical exception - Fovargue, Sara (Taylor & Francis, 2016)
Whenever the legitimacy of a new or ethically contentious medical intervention is considered, a range of influences will determine whether the treatment becomes accepted as lawful medical treatment. The development and introduction of abortion, organ donation, gender reassignment, and non-therapeutic cosmetic surgery have, for example, all raised ethical, legal, and clinical issues. This book examines the various factors that legitimatise a medical procedure. Bringing together a range of internationally and nationally recognised academics from law, philosophy, medicine, health, economics, and sociology, the book explores the notion of a treatment, practice, or procedure being proper medical treatment, and considers the range of diverse factors which might influence the acceptance of a particular procedure as appropriate in the medical context. Contributors address such issues as clinical judgement and professional autonomy, the role of public interest, and the influence of resource allocation in decision-making. In doing so, the book explores how the law, the medical profession, and the public interact in determining whether a new or ethically contentious procedure should be regarded as legitimate. This book will be of interest and use to researchers and students of bioethics, medical law, criminal law, and the sociology of medicine.